HABITUASI BAHASA JAWA KRAMA PADA PENUTUPAN PEMBELAJARAN UNTUK MEMBENTUK KARAKTER SOPAN SANTUN DI RA SALAFIYAH MARGOMULYO KEREK - Rr. Kusuma Dwi Ma’rifati; Ummidlatus Salamah; Liea Herlin (Institut Agama Islam Nahdlatul Ulama Tuban, 2022)
Abstract: This research is motivated by the erosion of character values, behavior, morals and manners and the disappearance of Javanese culture in the current generation. This study is intended to answer the following problems: (1) How is the application of Javanese manners habituation at the closing of the lesson to form the character of politeness in RA Salafiyah Margomulyo? (2) What are the problems of habituation of Javanese manners at the closing of the lesson to shape the character of manners at RA Salafiyah Margomulyo Kerek? (3) What is the solution for implementing the habituation of children in Javanese manners at the closing of the lesson to form a polite character at RA Salafiyah Margomulyo Kerek?. This research uses a qualitative research type and uses a descriptive approach which is carried out at RA Salafiyah Margomulyo, which is located in Margomulyo Village, Kerek District, Tuban Regency, East Java Province. The sources of data used in this study were the head of RA Salafiyah, teachers of RA Salafiyah, and students of RA Salafiyah. The results showed that the formation of polite character through the application of Javanese habituation of krama at the closing of the lesson to form polite character at RA Salafiyah Margomulyo went well.